Diagnostic value of combined detection of cryptococcal antigen in serum and lung puncture fluid using lateral flow assay for diagnosing pulmonary cryptococcosis: a single-center prospective study - Huang, Jinbao; Lin, Xinchen; Jiang, Meiqin; Li, Yangyu; Wang, Li; Xu, Shungui; Weng, Heng; Li, Hongyan; Ye, Ling (Frontiers in Microbiology, 2026)
ObjectiveTo evaluate the diagnostic value of the combined detection of cryptococcal antigen (CrAg) in the serum and lung puncture fluid (LPF) using a lateral flow assay (LFA) in patients with pulmonary cryptococcosis (PC).MethodsPatients with suspected PC were prospectively enrolled between June 2023 and July 2025 and underwent the IMMY CrAg LFA (Immuno-Mycologics, Norman, OK, United States) of serum and LPF specimens. Conventional fungal cultures were performed simultaneously and the diagnostic efficiencies of these methods for PC were compared.ResultsSamples were obtained from 167 patients, 33 with PC and 134 without PC. Among patients with PC, the sensitivity of serum CrAg testing was 75.8% [95% confidence interval (CI), 61.1–90.4%; 25/33] and that of LPF CrAg testing was 90.9% (95% CI, 81.1–100%; 30/33). The combination of serum and LPF testing increased the overall sensitivity of CrAg testing to 97.0% (95% CI, 91.2–100%; 32/33). The sensitivity, accuracy, and negative predictive value (NPV) of LPF culture were significantly lower than those of serum CrAg detection (P < 0.001, P = 0.002, and P < 0.001, respectively) and LPF CrAg detection (P < 0.001, P < 0.001, and P < 0.001, respectively); however, the diagnostic accuracy of serum and LPF CrAg detection did not differ significantly (P > 0.05). The sensitivity and NPV of serum and LPF CrAg detection combined were significantly higher than those of serum CrAg detection alone (P = 0.027 and P = 0.037, respectively). However, the accuracy of the two methods did not differ significantly (P = 0.061). Moreover, the area under the receiver operating characteristic curve for serum and LPF testing combined (0.981) was better than those for LPF culture (0.591), serum CrAg alone (0.875), and LPF CrAg alone (0.955).ConclusionSerum CrAg testing has superior sensitivity and accuracy compared to the conventional cryptococcal culture method using LPF, and CrAg testing of LPF samples further enhances diagnostic sensitivity. Moreover, detecting CrAg in serum and LPF specimens together provides high sensitivity and specificity, which significantly improves the diagnostic efficiency of PC.